A structural analytic method on the phase space data of Linac 4 MV photons based on the real world. (February 2021) - Cui, Zhenguo; Sha, Songlin; Bai, Yanling
Highlights: The presented characteristics of the fluence distribution of 4MV photons. The analyzed characteristics of the energy spectrum structure of 4MV photons. The method of collecting the primary and scatter photons was built. The work is a part of constructing the database of beams in radiotherapy. Abstract: Purpose: It was given that the characteristics of the fluence distribution and the energy spectrum structure of 4MV photons on the Phase Space (PhSp) plane and a method to analyzing the characteristics. Methods: After the PhSp file of 4 MV photons was acquired by the method of Monte Carlo (MC) calculation, the photons recorded by PhSp file were grouped based on the energy bin, and it was analyzed that the spatial distribution and energy spectrum structure of the photons. The photons in each energy group were continually grouped to sub-files according to momentum bin, and the primary and scattered photons could be separated according to the character of the fluence distribution of the photons in the sub-files. Results: The energy of 4 MV beam is a continuous spectrum. The energy constituent on a pixel at different distances from the center point is different, and the average energy on the center axis of the field is the highest; The photons with 0–1.0 MeV had 42.6% of all; that with energy more than 3.0 MeV had 11.7%; greater than 4 MeV, just 1.5%. The primary and scattered photons were easy collected according to the distribution characteristics of sub-groups. Conclusions: The work to acquire and analyze the PhSp file of the 4 MV beam is significant. 4 MV, 6 MV, 8 MV, 10 MV and 15 MV energy beams basically cover the beams of radiotherapy, and a database of the energy beams could be built for the MC related research of other scholars.